ANIMAL PHYSIOLOGY : adaptation and environment - Schmidt-Nielsen, Knut, 1915- (Cambridge ; New York : Cambridge University Press, 1990)
This edition of "Animal Physiology" has been fully revised and updated and provides a survey emphasizing fundamental principles rather than details. The text is written for those who want to know how things work, what animals do, and how they do it.
t t
Includes index
Keywords: Animal -- Physiology; Physiology